One political economy, one competitive strategy? - Herrmann, Andrea M. (Oxford University Press, 2008)
This book examines how firms adapt to the pressures of increasing international competition by testing the arguments on "strategy specialization" proposed in the competitiveness literature in general, and by contributors to the "varieties of capitalism" debate in particular. If different economies are characterized by distinct institutional arrangements, successful firms would be those that exploit the related comparative advantages and specialize in the competitive strategies facilitated by national institutions.